Cardiac CT assessment of tissue thickness at the ostium of the left atrial appendage predicts acute success of radiofrequency ablation. Issue 11 (23rd October 2017) - Whitaker, John; Panikker, Sandeep; Fastl, Thomas; Corrado, Cesare; Virmani, Renu; Kutys, Robert; Lim, Eric; O'Neill, Mark; Nicol, Ed; Niederer, Steven; Wong, Tom
Abstract: Background: Tissue thickness at the site of ablation is a determinant of lesion transmurality. We reported the feasibility, safety, and efficacy of longstanding persistent atrial fibrillation ablation, incorporating deliberate left atrial appendage (LAA) isolation and occlusion, and identified systematic differences in ostial LAA tissue thickness in a matched cohort of cadaveric specimens. Methods: Preprocedural cardiac computed tomography (CCT) scans were acquired from 22 patients undergoing LAA isolation and subsequent occlusion. Using a novel CCT wall thickness algorithm, LAA ostial wall thickness was assessed in vivo, compared with measurements from the cadaveric specimens, and analyzed for differences between regions that demonstrated acute electrical reconnection and those that did not. Results: Mean tissue thickness calculated for each LAA ostial quadrant was 2.1 (±0.6) mm (anterior quadrant), 1.9 (±0.4) mm (superior quadrant), 1.5 (±0.4) mm (posterior quadrant), and 1.8 (±0.7) mm (inferior quadrant). Tissue was significantly thicker in the anterior (P = 0.004) and superior quadrants (P = 0.014) than the posterior quadrant. Higher thickness measurements were recorded from quadrants demonstrated to be thicker from histology. Tissue was significantly thicker in regions that demonstrated acute electrical reconnection (1.9 (±0.6) mm) when compared with those that did not (1.6 (±0.5) mm) (P = 0.008). Conclusions: CCT imaging may be used to detect differences in wall thickness at different atrial locations and success of LAA ablation may be affected by local tissue thickness. Atrial wall thickness may need to be considered as a metric to guide titration of radiofrequency energy for safe and successful ablation.